Perkembangan Motorik Prasekolah antara Intervensi Brain Gym dengan Puzzle - Panzilion Panzilion; Padila Padila; Gita Tria; Muhammad Amin; Juli Andri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aims to determine the Comparison of the Effectiveness of Brain Gym and Puzzle Playing Against the Development of Fine Motorcycles in Preschoolers in the Work Area of ​​the Basuki Rahmad Community Health Center in Bengkulu City. Quantitative research design using the Quasy Experiment design, two groups of pre-post tests equivalent without control design. The results of univariate analysis with brain gym intervention, from 15 respondents before the brain gym there were 9 children (60%) experienced deviant fine motor skills and after given 11 children therapy (73.3%) experienced normal fine motor skills. Whereas from the 15 respondents before intervening tubuzzle, there were 8 children (53.3%) having deviated fine motor skills and after being given a puzzle 15 respondents (100%) experienced normal fine motor skills. The bivariate results of Wilcoxon test have the effect of brain gym with p-value = 0,000 and puzzle with p-value = 0.001 in the development of fine motor in preschool children. Mann Whitney test results obtained p-value = 0.005. Conclusion, playing puzzles was more effective in the development of fine motor skills of preschoolers in the Basuki Rahmad Community Health Center in the City of Bengkulu. Keywords: Brain gym, Motor, Preschool, Puzzle